LncRNAs 60248.51 and 9826.1 are identified as potential regulators of endometrial receptivity in Tibetan Northwest Cashmere goats - SUO, Langda (2023)
Endometrial receptivity is a key determinant of embryo implantation, which is the initial step of a successful pregnancy. In this study, high-throughput RNA sequencing was conducted in pre-receptive endometrium (PE) and receptive endometrium (RE) derived from Tibetan Northwest Cashmere goats. There were only a handful of miRNAs and circRNAs differentially expressed between PE and RE tissues, while there were 250 upregulated coding genes and 193 upregulated lncRNAs and 135 downregulated coding genes and 123 downregulated lncRNAs in RE tissues, suggesting the predominant role of coding genes and lncRNAs in the regulation of endometrial receptivity. Moreover, gene ontology and Kyoto Encyclopedia of Genes and Genomes analyses revealed that differentially expressed lncRNAs are significantly enriched in Wnt, Hedgehog, and Hippo signaling pathways. Furthermore, the two most upregulated lncRNAs, MSTRG.60248.51 (1264 bp) and MSTRG.9826.1 (1362 bp), were screened as candidate lncRNAs, and both upregulation of 60248.51 and 9826.1 could activate Wnt and Hippo signaling and promote cell viability, migration, and secretion of endothelin-1, epidermal growth factor, and colony stimulating factor in primary goat endometrial epithelial cells. In summary, lncRNAs 60248.51 and 9826.1, identified as potential regulators of endometrial receptivity in Tibetan Northwest Cashmere goats, improve cell viability, migration, and secretion functions in endometrial epithelial cells, which may be associated with the Wnt and Hippo signaling pathways. Keywords: Tibetan Northwest cashmere goats; endometrial receptivity; lncRNA 60248.51 and lncRNA 9826.1; primary goat endometrial epithelial cells; the Wnt and Hippo signaling pathways.